The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11669-008-9424-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Interface Reaction Between Titanium and the Eutectic Silver-Copper Brazing Alloy

Abstract: Reaction zones formed at 790 °C between solid titanium and liquid Ag-Cu eutectic alloys (pure and Ti-saturated) have been characterized. When pure Ag-Cu eutectic alloy with 40 at.% Cu is used, the interface reaction layer sequence is: αTi / Ti 2 Cu / TiCu / Ti 3 Cu 4 / TiCu 4 / L. Because of the fast dissolution rate of Ti in the alloy, the reaction zone remains very thin (3-6 µm) whatever the reaction time. When the Ag-Cu eutectic alloy is saturated in titanium, dissolution no longer proceeds and a thicker re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
4
18
1
Order By: Relevance
“…The formation of the Cu 4 Ti 3 phase (layer 5) in the SS/Ti BZ was also reported in other investigations. [12,13,20,[34][35][36] However, contrary to the present observations, Shiue et al [19] and Shafiei et al [20] reported the formation of the Cu 4 Ti phase in the BZ, whereas they did not report the formation of Cu 3 Ti 2 phase which formed conspicuously in the present study. Andrieux et al [40] in an experimental investigation on the phase stability study on the Cu-Ti system showed that the Cu 3 Ti 2 phase is stable and can form by solid state reaction in a temperature range of 1063 K to 1133 K (790 C to 860 C).…”
Section: B Phase Formation In the Braze Zonecontrasting
confidence: 99%
See 2 more Smart Citations
“…The formation of the Cu 4 Ti 3 phase (layer 5) in the SS/Ti BZ was also reported in other investigations. [12,13,20,[34][35][36] However, contrary to the present observations, Shiue et al [19] and Shafiei et al [20] reported the formation of the Cu 4 Ti phase in the BZ, whereas they did not report the formation of Cu 3 Ti 2 phase which formed conspicuously in the present study. Andrieux et al [40] in an experimental investigation on the phase stability study on the Cu-Ti system showed that the Cu 3 Ti 2 phase is stable and can form by solid state reaction in a temperature range of 1063 K to 1133 K (790 C to 860 C).…”
Section: B Phase Formation In the Braze Zonecontrasting
confidence: 99%
“…[12,13,20,34,35] This phase also formed in the interaction zone during the solid-liquid reaction between Ti and Ag-Cu alloys [19,36] and solid-solid reactive diffusion between Ti and Cu. [29] Laik et al [29] demonstrated that during the reactive diffusion of Cu and Ti, CuTi is the first one to form in the diffusion zone, using the ''effective heat of formation model.''…”
Section: B Phase Formation In the Braze Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, during temperature rise to 900°C the kinetics of dissolution of Ti in Ag-40at.%Cu eutectic is significantly reduced by the formation at solid Ti/liquid AgCu interface of different Cu x Ti y compounds such as Cu 4 Ti, Cu 3 Ti 4 or CuTi [31]. As a consequence the effective activity of Ti in the drop is lower than the nominal one.…”
Section: Ti-containing Ag-40at%cu Eutectic Alloysmentioning
confidence: 99%
“…It was suggested that copper has a strong tendency to rapid formation of intermetallics with titanium, and Ag is the less active element of Ag-Cu filler alloys with low diffusivity through the CuTi layer; however, the presence of Ag can remarkably increase the activity of filler alloys to promote interfacial reactions with technically stable ceramics [9,22,23]. Other elements such as V, Cr, Zr, V, Nb, Ta and Hf can also be considered chemically active in braze alloys composition -especially Ti, which can make chemical interactions (dissolution, interdifusion and/or product formation reaction) at the ceramic/metal interfaces to enhance wetting on the ceramic surface [5,6,24].…”
Section: Microstructural Analysismentioning
confidence: 99%